MYSIR 2022 Virtual E-Abstract 3 - Interventional Radiology, Malaysian Society of (The Interventionalist Journal, 2022)
1. HOW TO GET OUT OF JAIL: AN ENDOVASCULAR APPROACH TO A MAL-POSITIONED CENTRAL VENOUS DIALYSIS CATHETER FROM LEFT SUBCLAVIAN ARTERY TO LEFT VENTRICLE 2. HOW TO GET OUT OF JAIL: AN ENDOVASCULAR APPROACH TO A MAL-POSITIONED CENTRAL VENOUS DIALYSIS CATHETER FROM LEFT SUBCLAVIAN ARTERY TO LEFT VENTRICLE 3. TUNNELED ADULT PERIPHERALLY INSERTED CENTRAL CATHETER (PICC) FOR CENTRAL VENOUS ACCESS IN PEDIATRICS: A SINGLE CENTRE EXPERIENCE 4. POST TRAUMATIC FACIAL PAIN; MULTIFACTORIAL CAUSES AND ROLE OF MINIMALLY INVASIVE PAIN INTERVENTION TREATMENT OPTIONS 5. A RARE CASE OF MECKEL’S DIVERTICULUM IN ELDERLY PRESENTED WITH GASTROINTESTINAL BLEED WITH MULTIPLE INTRAABDOMINAL SMALL VESSELS PSEUDOANEYRYSM